PELATIHAN PEMBUATAN KRUPUK UNTUK MEMBANTU PEREKONOMIAN IBU-IBU DESA MUDUNG KEPOHBARU BOJONEGORO. - M.Azuz Shony Azhar; Ayu Rohmana; Anis Mafulah (LPPM Universitas Islam Darul 'Ulum Lamongan, 2020)
KeyOnion crackers are one type of crackers whose basic ingredients use tapioca flour. Besides being cheap and easy to get, these onion crackers are also very popular with the public. In addition, the shape of onion crackers in the community so far is only mediocre, namely round oval, so it needs creativity in making onion crackers by making onion crackers into other forms that are more interesting. The shape of crackers, basic ingredients and packaging can also affect the economic value of crackers. The problem in this study is the existence of problems in the economic field in the household, the lack of income in the family because it only depends on one family backbone. so that in this study aims at the existence of new innovations from making onion crackers are expected to help the family economy, especially for mothers in the village of Mudung, Kepobaru District, Bojonegoro Regency.